Image Analysis for Ophthalmological Diagnosis Image Processing of Corvis® ST Images Using Matlab® - Koprowski, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph focuses on the use of analysis and processing methods for images from the Corvis® ST tonometer. The presented analysis is associated with the quantitative, repeatable and fully automatic evaluation of the response of the eye, eyeball and cornea to an air-puff. All the described algorithms were practically implemented in MATLAB®. The monograph also describes and provides the full source code designed to perform the discussed calculations. As a result, this monograph is intended for scientists, graduate students and students of computer science and bioengineering as well as doctors wishing to expand their knowledge of modern diagnostic methods assisted by various image analysis and processing methods.
Introduction -- Image pre-processing -- Main Image processing -- Additional Image Processing and Measurement -- Impact of Image Acquisition and Selection of Algorithm Parameters on the Results -- Summary of Measured Features -- Conclusions.
Keywords: Computational intelligence; Artificial intelligence; Ophthalmology; Computational Intelligence; Artificial Intelligence; Ophthalmology